2015
DOI: 10.3892/etm.2015.2205
|View full text |Cite
|
Sign up to set email alerts
|

Association between implant apex and sinus floor in posterior maxilla dental implantation: A three-dimensional finite element analysis

Abstract: The aim of the present study was to evaluate the effect of the association between the implant apex and the sinus floor in posterior maxilla dental implantation by means of three-dimensional (3D) finite element (FE) analysis. Ten 3D FE models of a posterior maxillary region with a sinus membrane and different heights of alveolar ridge with different thicknesses of sinus floor cortical bone were constructed according to anatomical data of the sinus area. Six models were constructed with the same thickness of cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
0
9
0
5
Order By: Relevance
“…Finally, the cortical bone surrounding the maxillary sinus and mandibular canal can be extremely thin, up to 1 mm (Yan et al 2015), or of an intermediate density between cancellous and cortical. These anatomic variations may not provide as much tissue contrast as provided in the bulk tissues measured here.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the cortical bone surrounding the maxillary sinus and mandibular canal can be extremely thin, up to 1 mm (Yan et al 2015), or of an intermediate density between cancellous and cortical. These anatomic variations may not provide as much tissue contrast as provided in the bulk tissues measured here.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical situations, however, these phenomena are not likely to occur as the bone loss occurs continuously. In preliminary modelling, the maxillary bone was reconstructed from the data of other researchers [ 15 ][ 16 ] according to the anatomical area of the sinus.…”
Section: Discussionmentioning
confidence: 99%
“…For immediate loading, when the implant apex broke into or through the sinus cortical bone, the maximum displacements of the implant, particularly at the implant apex, were smaller than those did not reach sinus floor. Yan et al [ 16 ] FE study on the association between implant apex and sinus floor showed that having the implant apex in contact with, piercing or breaking through the sinus floor cortical bone benefited the implant stability, particularly for immediate loading.…”
Section: Discussionmentioning
confidence: 99%
“…Bone quality is proven to be one of the critical determinants for implant treatment planning [ 15 ]. Nevertheless, due to poor bone quality, the implant success rates in the posterior maxillary regions were lower than in other regions [ 32 , 33 ]. In this case, an attempt was undertaken to investigate the impact of bone quality on the stress magnitude of supporting bone and emphasis on D3 and D4 bone.…”
Section: Discussionmentioning
confidence: 99%